The Influence of Work Motivation and Job Satisfaction on Employee Performance at the Artha Medika Farma Health Clinic and Pharmacy, Palopo City - Leowirantho, Muhammad Ridho; Yusuf, Ria Mardiana; Hakim, Wardani (Pascasarjana STIE Amkop Makassar, 2023)
The aim of this research is to analyze and find out how the variables of work motivation and job satisfaction influence the performance of employees at the Artha Medika Farma Health Clinic and Pharmacy in Palopo City. This research was conducted at the Artha Medika Farma Health Clinic and Pharmacy, Palopo City by distributing questionnaires to 30 respondents. The measurement scale uses a Likert scale. Data were analyzed using multiple linear regression. Research hypothesis testing uses the t test and F test techniques with the SPSS auxiliary route. The results of this research show that work motivation and job satisfaction each have a positive and significant influence on the performance of employees at the Artha Medika Farma Health Clinic and Pharmacy in Palopo City.Keywords:Work motivation, job satisfaction and performance.